2021
DOI: 10.1016/j.ensci.2021.100320
|View full text |Cite
|
Sign up to set email alerts
|

Cases of neuromyelitis optica spectrum disorder from the East Africa region, highlighting challenges in diagnostics and healthcare access

Abstract: Background Neuromyelitis optica spectrum disorder (NMOSD) is an auto-immune disease of the central nervous system (CNS) associated with the IgG-antibody against aquaporin-4 (AQP4-IgG). There is little published epidemiology of NMOSD from sub-Saharan Africa (SSA). Methods We retrospectively collated NMOSD cases admitted to our tertiary regional neurology centre. Results We identified 11 cases (10 female, average age 30 years). 64% (7/11) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…However, adult age has often been found in the literature [8]. The average age of our patients (38.3 years) is within the age range of 20 -50 years reported in many African studies focusing on autoimmune diseases of the nervous system [21] [49]- [58].…”
Section: Discussionsupporting
confidence: 52%
“…However, adult age has often been found in the literature [8]. The average age of our patients (38.3 years) is within the age range of 20 -50 years reported in many African studies focusing on autoimmune diseases of the nervous system [21] [49]- [58].…”
Section: Discussionsupporting
confidence: 52%
“…10,11 The variations in clinical and radiological features have been reported among different races as well as between different serostatuses and age groups. 12 Few studies of NMOSD have been reported from Africa and Middle East, [13][14][15][16][17][18][19] and so far in such heavily populated African country like Egypt, only two studies of NMOSD were conducted in Egypt. 20,21 To our knowledge, the detailed radiological characteristics of NMOSD were not studied before among the Egyptian population.…”
mentioning
confidence: 99%